Experimental and Computational Studies on Regiodivergent Chiral Phosphoric Acid Catalyzed Cycloisomerization of Mupirocin Methyl Ester. Issue 20 (18th March 2020) - Wang, Sibin; Arguelles, Alonso J.; Tay, Jia‐Hui; Hotta, Miyuki; Zimmerman, Paul M.; Nagorny, Pavel
Abstract: This article presents a new strategy for achieving regiocontrol over the endo versus exo modes of cycloisomerizations of epoxide‐containing alcohols, which leads to the formation of five‐ or six‐membered cyclic ethers. Unlike traditional methods relying on achiral reagents or enzymes, this approach utilizes chiral phosphoric acids to catalyze the regiodivergent selective formations of either tetrahydrofuran‐ or tetrahydropyran‐containing products. By using methyl ester of epoxide‐containing antibiotic mupirocin as the substrate, it is demonstrated that catalytic chiral phosphoric acids ( R )‐TCYP and ( S )‐TIPSY could be used to achieve the selective formation of either the six‐membered endo product (95:5 r.r.) or the five‐membered exo product (77:23 r.r.), correspondingly. This cyclization was found to be unselective under the standard conditions involving various achiral acids, bases, or buffers. The subsequent mechanistic studies using state‐of‐the‐art quantum chemical solutions provided the description of the potential energy surface, which is fully consistent with the experimental observations. Based on these results, highly detailed reaction paths are obtained and a concerted and highly synchronous mechanism is proposed for the formation of both exo and endo products. Abstract : endo vs . exo : Chiral phosphoric acid catalysts are used for achieving regiocontrol over the endo vs. exo modes of cycloisomerizations of epoxide‐containing antibiotic mupirocin methyl ester. This approach utilizes chiral phosphoric acids to catalyze the regiodivergent selective formations of either tetrahydrofuran‐ or tetrahydropyran‐containing products. The mechanism of these reactions is investigated by using state‐of‐the‐art quantum chemical solutions.